The Relationship Between Vitamin E Intake and HDL (High Density Lipoprotein) Level in Elderly Hypertensive Patients at Setabelan Health Center Banjarsari Surakarta - Fajriyah, Izzatul (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Old age is a vulnerable period for health problems. One of the frequently occurring diseases is hypertension. Hypertension can lead to damage to the arterial endothelium, thereby accelerating atherosclerosis. This condition results in disturbances in lipid metabolism and abnormalities in lipid profiles. Vitamin E can function as an antioxidant in the cholesterol metabolism process, protecting Low-Density Lipoprotein from oxidation and increasing High-Density Lipoprotein. An increase in the level of High-Density Lipoprotein occurs when Cholesterol Ester Transfer Protein activity decreases. CETP activity is influenced by antioxidant compounds like vitamin E. The aim of this research is to determine the relationship between vitamin E intake and High-Density Lipoprotein levels in elderly individuals with hypertension at the Setabelan Community Health Center, Banjarsari, Surakarta. This research is of observational nature with a cross-sectional approach. The research participants were 72 elderly individuals with hypertension at the Setabelan Community Health Center, selected through convenience sampling. Data collection was performed by measuring High-Density Lipoprotein levels using a spectrophotometer with the Cholesterol Oxidase-P-Amino Phenazone method and assessing vitamin E intake using a Semi-Quantitative Food Frequency Questionnaire over the past month. Data analysis involved univariate and bivariate analyses using the Rank Spearman test. The research results indicate that the distribution of samples based on vitamin E intake is mostly insufficient (98.6%). The distribution of samples based on High-Density Lipoprotein levels is mostly high (61.1%). The Rank Spearman analysis (p<0.05) between vitamin E intake and High-Density Lipoprotein levels yielded a p-value of 0.0433. In conclusion, there is no relationship between vitamin E intake and High-Density Lipoprotein levels in elderly individuals with hypertension at the Setabelan Community Health Center, Banjarsari, Surakarta.